Estudo da influência do glicerol no processo de deposição de ligas Zn-Mn e nos depósitos de Zn-Mn - Araújo, Eliene Leandro de (2011)
The influence of glycerol additive on the electrodeposition process of Zn-Mn on Pt substrate from acid baths by means of cyclic voltammetry and the characteristics of the coatings by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectrometry (EDS) and of X-ray diffraction (XRD) have been studied. The voltammograms for deposition of Zn-Mn obtained with 0 to 0.63 M glycerol and boric acid 0.080 M or 0.24 M, were, in general similar (presence of the cathodic wave c0, two cathodic peaks c1 and c2, an anodic peak a1 and a2 region formed by an anodic waves). The efficiency of the process of electrodeposition of Zn-Mn increased with the concentration of glycerol and was it lower than 100%. The analyses of the coatings by SEM showed that those obtained in the deposition potential of -1.19 V were not uniform, consisting of crystallites of different sizes. The only exception was for the deposit obtained with GLY 0.32 M which was more uniform and covered all the substrate of Pt. The electrodeposit analysis obtained by EDX did not indicate this Edep codeposition of Mn with Zn for most of the coatings while for some we cannot assure the presence of Mn. Those obtained at Edep= - 1.53 V from baths containing 0.080 M - 0.48 M GLY were dendritic, while the ones obtained in the presence of 0.63 M GLY were refined showing that this concentration of glycerol acted as a brightener. The XRD analyses showed that the electrodeposits were formed from Zn, Mn, oxides and alloys of different compositions. The smaller size of the glycerol molecule related to boric-sorbitol complex did not prevent the codeposition of Zn and Mn did not lead to a more compact deposit and did not significantly alter the composition of phases.